Identifikasi Perubahan Mutu Selama Penyimpanan Buah Manggis Menggunakan Near Infra Red Spectroscopy - . Sutrisno; Yohanes Aris Purwanto; Emmy Darmawati; Enrico Syaefullah (Jurnal Ilmu Pertanian Indonesia, 2012)
One of quality changes during storage of intact mangosteen fruit is firmness. This occurrence was predicted to have associate with moisture content in the pericarp. The objective of this research was to determine the correlation between moisture content and firmness, and to predict moisture content changes based on reflectance spectrum of near infra red (NIR). The correlation between moisture content and firmness at 13 °C is y = 0.07972x2 – 9.833x + 305.9 while at room temperature showed y = 0.1207x2 – 14.89x + 460.8; in which y refers to firmness and x refers to moisture content in pericarp. The calibration and validation evaluation using partial least square of moisture content resulted in NIR and oven method showed that the magnitude of r is 0.758-0.882; RMSEC and RMSEP is 0.09-0.39%; CV<5% is at 2.5-3.3%. Moisture content prediction using NIR reflectant spektrum is y (temperature:8 °C) = -0.057x + 65.14; y (temperature 13 °C) = -0.253x + 64.96; y (room temperature) = -0.421x + 64.76.